Cinchona amazonica Standl. (Rubiaceae) in the state of Acre, Brazil - Pollito, Percy Amilcar Zevallos; Filho, Mário Tomazello (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The present research is about dendrology, geographic distribution and status of conservation of Cinchona amazonica Standl. with are plants with medical interest; they grow in the state of Acre, Brazil. The research consisted in: field work for the collection of botanical material, in the survey and study of the available exsiccates in the national and international herbariums of the South America. It has been done a bibliographical review of the species of this genera in literature and the specialized sites The results present the description of the species with their illustration and mapping, as well as determination of their population situation.
Keywords: Cinchona; Dendrology; Geographic distribution; Conservation status; Acre